Avenger - Forsyth, Frederick (Transworld Publishers, 2003)
A young American aid volunteer, Ricky Colenso, is brutally murdered in former Yugoslavia. His grandfather, the Canadian billionaire Steven Edmond, is bent on revenge. The quest to find Ricky's murderer leads Edmond to Cal Dexter, ex-Vietnam Special Forces, the one man who could bring the killer to justice. But what starts as a personal, domestic tragedy soon explodes into a terrifying drama on the centre stage of world terrorism.
Keywords: Fiction